Bibliometric contributions to the field of educational research (2019)
This article presents the bibliometric results as a product of a methodological and epistemological approach to transitions, occurring in the field of educational research from scientific publications of the Universidad PedagógicaNacional, Universidad de Antioquia, and Universidad de la Sabana. In this context, magazines operate as documentary communication instruments into the framework of education and pedagogy; from which the various analyzes of the Law of Bradford, Lotka’s Law and the Price Law were made. However, the results achieved in 147 researches in education and pedagogy are still inadequate according to the analyzed records.